2020
DOI: 10.3390/healthcare8040519
|View full text |Cite
|
Sign up to set email alerts
|

Design, Assessment, and Validation of a Questionnaire to Estimate Food-Dependent Exercise-Induced Anaphylaxis Prevalence in Latin American Population

Abstract: There are no epidemiological data about food-dependent exercise-induced anaphylaxis (FDEIA) in Latin America. Our aim was to design, assess, and validate a questionnaire to identify potential FDEIA cases and/or estimate its prevalence by self-report. Questions were included in the instrument to address the main symptoms of FDEIA, type/intensity of physical activity, and anaphylaxis. The instrument’s clarity, comprehension and repeatability were evaluated. These evaluations were carried out by Hispanic people (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…2 We believe that questionnaires translated into a different language or new sections designed should be evaluated at least for clarity and comprehension to ensure the correct interpretation of the questionnaire. 3,4 Second, the authors define self-reported NCGS as the reporting of symptoms at least once a week after gluten intake and a visual analog scale score of symptom discomfort ≥ 8. However, the rationale for an undemanding NCGS definition should be given since, from some studies, 5,6 some questions could be raised: why not consider the triggering of the symptoms always or most of the time after gluten ingestion?…”
mentioning
confidence: 99%
“…2 We believe that questionnaires translated into a different language or new sections designed should be evaluated at least for clarity and comprehension to ensure the correct interpretation of the questionnaire. 3,4 Second, the authors define self-reported NCGS as the reporting of symptoms at least once a week after gluten intake and a visual analog scale score of symptom discomfort ≥ 8. However, the rationale for an undemanding NCGS definition should be given since, from some studies, 5,6 some questions could be raised: why not consider the triggering of the symptoms always or most of the time after gluten ingestion?…”
mentioning
confidence: 99%